New global uncertainties and its meaning for European Union integration? - Mascitelli, Bruno (AEI Insights, 2021)
The concept of European Union integration has been at the forefront of much discussion on what the future of the European Union project would be. At various junctions, especially in crisis times, the concept of integration would be code for a balance sheet on its progress and future challenges. The uncertainties that have merged since the British referendum decision to leave the European Union in June 2016, has provided a new framework for the future of European integration. It has seen the first departure of a member, and not an insignificant member, from the Union alongside destabilizing features in the world order. The dismissive approach from the Trump administration and the volatility of US foreign policy has put many in the EU on tender hooks. Moreover, European Union member states have had to contend with a volatile Euro-sceptic electorate, which has blamed the European Union for a crisis of expectations. The election results in 2017 in The Netherlands, and the victory of Macron in France, provided for some, reason to believe that not all was lost. The leadership of the European Union has taken a sober approach towards the current crisis and has refrained from submission to this pessimism. Though locked in negotiations with the UK over Brexit, its release of the White Paper on the future of the European Union issued in March 2017 was an attempt to insure that Brussels and the EU was not ruling from on–high without member state buy in. It was a document which was partially defensive (only mentioning Brexit once) but at the same time seeking a guide on whether, and how, to approach future European Union integration.